Runx1 is required for zebrafish blood and vessel development and expression of a human RUNX1-CBF2T1 transgene advances a model for studies of leukemogenesis - Kalev-Zylinska, Maggie L.; Horsfield, Julia A.; Flores, Maria Vega C.; Postlethwait, John H.; Vitas, Maria R.; Baas, Andrea M.; Crosier, Philip S.; Crosier, Kathryn E. (Development (Cambridge), 2002)
RUNX1/AML1/CBFA2 is essential for definitive hematopoiesis, and chromosomal translocations affecting RUNX1 are frequently involved in human leukemias. Consequently, the normal function of RUNX1 and its involvement in leukemogenesis remain subject to intensive research. To further elucidate the role of RUNX1 in hematopoiesis, we cloned the zebrafish ortholog ( runx1 ) and analyzed its function using this model system. Zebrafish runx1 is expressed in hematopoietic and neuronal cells during early embryogenesis. runx1 expression in the lateral plate mesoderm co-localizes with the hematopoietic transcription factor scl , and expression of runx1 is markedly reduced in the zebrafish mutants spadetail and cloche . Transient expression of runx1 in cloche embryos resulted in partial rescue of the hematopoietic defect. Depletion of Runx1 with antisense morpholino oligonucleotides abrogated the development of both blood and vessels, as demonstrated by loss of circulation, incomplete development of vasculature and the accumulation of immature hematopoietic precursors. The block in definitive hematopoiesis is similar to that observed in Runx1 knockout mice, implying that zebrafish Runx1 has a function equivalent to that in mammals. Our data suggest that zebrafish Runx1 functions in both blood and vessel development at the hemangioblast level, and contributes to both primitive and definitive hematopoiesis. Depletion of Runx1 also caused aberrant axonogenesis and abnormal distribution of Rohon-Beard cells, providing the first functional evidence of a role for vertebrate Runx1 in neuropoiesis. To provide a base for examining the role of Runx1 in leukemogenesis, we investigated the effects of transient expression of a human RUNX1-CBF2T1 transgene [product of the t(8;21) translocation in acute myeloid leukemia] in zebrafish embryos. Expression of RUNX1-CBF2T1 caused disruption of normal hematopoiesis, aberrant circulation, internal hemorrhages and cellular dysplasia. These defects reproduce those observed in Runx1-depleted zebrafish embryos and RUNX1-CBF2T1 knock-in mice. The phenotype obtained with transient expression of RUNX1-CBF2T1 validates the zebrafish as a model system to study t(8;21)-mediated leukemogenesis.